Akhlak dalam Islam - Aulia, Nurul (Maliki Interdisciplinary Journal, 2024)
Morals are a very important aspect in Islamic teachings. Morals refer to the behavior, attitudes and ethics that a Muslim should have. This research aims to explore the concept of morals in Islam, its sources, and its application in everyday life. Through a comprehensive literature study, this research analyzes verses from the Koran, hadith, and the works of leading scholars to understand the definition, principles, and examples of noble morals in Islam. The research results show that morals in Islam originate from the Al-Quran, the Sunnah of the Prophet Muhammad SAW, and the legacy of knowledge from the ulama. Good morals include honesty, patience, humility, compassion and concern for others. Bad morals such as lying, jealousy, arrogance and cruelty must be avoided. This research concludes that noble morals are a reflection of true faith and are the basis for creating a harmonious and dignified society.